Northeastern united states species treated with copper-based preservatives: Durability in mississippi stake tests - T. Lebow, Stan; A. Arango, Rachel; K. Lebow, Patricia; T. Kirker, Grant; E. Mankowski, Mark; A. Halverson, Steven (Maderas. Ciencia y Tecnología, 2018)
This paper reports on the ground-contact durability of lesser-used wood species of the northeastern United States after treatment with copper-based preservatives. Stakes (19 by 19 by 457 mm) cut from balsam-fir (Abies balsamea), eastern hemlock (Tsuga canadensis), eastern spruce (mixture of Picea glauca, Picea mariana and Picea rubens), red maple (Acer rubrum) or eastern white pine (Pinus strobus) were treated with one of four concentrations of chromated copper arsenate type C (CCA-C), copper citrate (CC), alkaline copper quat type C (ACQ-C) or copper azole type A (CBA-A) and placed into the ground at a test site in southern Mississippi. Similarly treated southern pine (Pinus spp.) stakes were included for comparison. The stakes were rated for decay and termite attack after 1, 2, 3, 4, 5, 8, 10 and 12 years. Eastern white pine and incised eastern hemlock and balsam-fir had durability similar to southern pine when treated with CCA or the other copper-based preservatives. Eastern spruce was less durable than the other softwood species, apparently because of low preservative uptake. Red maple had the least durability at all retentions and for all preservatives. This study indicates that several northeastern softwoods can be adequately durable when pressure-treated with CCA-C or copper-based preservatives.